TIMBER BOOM IN EAST KALIMANTAN (1967–1971): ECONOMIC GROWTH AND ENVIRONMENTAL IMPACT - Marfuah, Siti; Azmi, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
Between 1967 and 1971, East Kalimantan witnessed a rapid increase in timber exploitation, commonly known as the